Manufacturing a Refrigerator with Heat Recovery Unit (Journal of University of Babylon for Engineering Sciences, 2018)
This study aims to exploite the rejected heating energy from condenser and benefit from it to reheat the foods and other materials. It can also be employed to improve the coefficient of performance of a refrigerator at the same time by using approximately the same consumption electrical energy used to operate the compressor and refrigerator in general. This idea has been implemented by manufacturing of a refrigerator with using additional part has the same metal and condenser pipe diameters but its surface area does not exceed 40% from total surface area of the condenser and its design as an insulated cabinet from all sides to prevent heat leakage through it and located between the compressor and the condenser. Small electrical fan has been added inside this cabinet to provide a suitable air circulation and a homogenous temperature distribution inside the cabinet space. It is expected that the super heating energy of refrigerant (R134a) which comes out of the compressor would be removed  inside this cabinet and this insist to condensate the refrigerant (cooling fluid) with a rate higher than that used in the normal refrigerator only. Three magnetic valves have been used in order to control the refrigerant flow in state of operation the refrigerator only or to gather with heating cabinet. To measure the temperatures at each process of the simple vapor compression refrigeration cycle, nine temperature sensors at input and output of each compressor, condenser and an evaporator in additional to input of cabinet and inside it and on evaporator surface have been provided. Five pressure gages have been used to measure the value of pressure and compare it for the two states of operation. The consumption of electrical energy  can be calculated by adding an ammeter and a voltmeter and compare between the consumption energy of both states. The obtained results show that there is an improvement in the coeffecient of performance in state of operation the refrigerator with heat recovery cabinet by 20% more than that of the operation of refrigerator only. This improvement is due to the reduction in the condenser exit temperature by 4 to 6 C˚, and the super heat removing process in reheating cabinet. The temperature of the cabinet reachs to 60 C˚ which is a sufficient for the food heating. A small amount of refrigerant pressure reduction due to these additions, and its effect on the preformace of the refrigerator  may be not considerable.